2021
DOI: 10.3389/fimmu.2021.599014
|View full text |Cite
|
Sign up to set email alerts
|

Innovations and Advances in Schistosome Stem Cell Research

Abstract: Schistosomes infect about 250 million people globally causing the devastating and persistent disease of schistosomiasis. These blood flukes have a complicated life cycle involving alternating infection of freshwater snail intermediate and definitive mammalian hosts. To survive and flourish in these diverse environments, schistosomes transition through a number of distinct life-cycle stages as a result of which they change their body plan in order to quickly adapt to each new environment. Current research sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Currently no human vaccines are available and, as clinical treatment relies entirely on the single drug praziquantel, the potential emergence of drug resistance is an ever-present concern (1). Recent studies have demonstrated that stem cells play vital roles in driving and maintaining the complex schistosome life cycle (4)(5)(6)(7)(8). Adult schistosomes parasitize mammals and lay eggs many of which eventually escape these definitive hosts in feces or urine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently no human vaccines are available and, as clinical treatment relies entirely on the single drug praziquantel, the potential emergence of drug resistance is an ever-present concern (1). Recent studies have demonstrated that stem cells play vital roles in driving and maintaining the complex schistosome life cycle (4)(5)(6)(7)(8). Adult schistosomes parasitize mammals and lay eggs many of which eventually escape these definitive hosts in feces or urine.…”
Section: Introductionmentioning
confidence: 99%
“…The fibroblast growth factor (FGF) signaling pathway in mammals is critically involved in a variety of processes during embryonic development and adult homeostasis through promoting cell proliferation, cell differentiation, cell survival, tissue repair/regeneration, drug resistance, and apoptosis (7,(11)(12)(13)(14)(15). Significantly, FGF signaling is crucial in stem cell control in various model systems including both vertebrates (5,(16)(17)(18) and invertebrates (14,(19)(20)(21)(22). The mammalian FGF pathway is activated by binding FGF ligands to FGFRs, thereby phosphorylating mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K)/AKT (protein kinase B, also called PKB), phospholipase C gamma (PLCg), and signal transducers and activators of transcription (STAT) (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it was shown that schistosomes, like the planarians, also contain stem cells. There are two major stem cells that play in the different life stages during intramolluscan and intramammalian development, including the germinal cells of sporocysts involved in asexual reproduction and the neoblast of adult worms involved in sexual reproduction [ 72 ]. Germinal cells have similar morphology with the neoblasts of planarians, they have a high nuclear to cytoplasmic ratio, an open chromatin structure and a large nucleolus [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another fledgling area where Australian vaccinologists can make a mark is the establishment of schistosome stem cell lines to advance schistosomiasis vaccine research [ 124 ]. The availability of such self-renewable resources can provide a new platform to study stem cell behavior and regulation, and to undertake studies on important areas of schistosome biology, reproductive development and survival.…”
Section: Insulin Receptors (Sjirs)mentioning
confidence: 99%
“…Another fledgling area where Australian vaccinologists can make a mark is the establishment of schistosome stem cell lines to advance schistosomiasis vaccine research [124].…”
Section: Insulin Receptors (Sjirs)mentioning
confidence: 99%